Sublayer effect near the wall in the presence of Svedov-Bingham flow - Chi, Nguyen Huu; Thanh, Pham Hoai (Vietnam Journal of Mechanics, 1994)
In this paper we study the stationary flow of viscous-plastic fluid in the horizontal cylindrical tube (Svedov Bingham's flow) with the assumption of existence of the viscous adherent sub layer near the wall. The obtained results are estimated and compared with those of Svedov - Bingham flow. We also inspect the "near the wall effect" which was showed in the work of Smoldurev & Xaponov and have some notes and estimation about it.